2019
DOI: 10.1002/pssb.201800356
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Defect‐Assisted UV–Visible Energy Conversion in Gd2O3:Er Nanoparticles

Abstract: The correlations between defectiveness and optical properties of Er‐doped Gd2O3 nanoparticles coupled into cubic and monoclinic crystal structures were studied employing XPS and PL spectroscopies. The main focus of this research is paid to the cubic Gd2O3 phase, which is more suitable for light‐emitting purposes. It is shown that oxygen‐related point defects are the precursors for the formation of cationic irregulars – “defective” Gd3+ ions with local energy levels in the energy band gap of Gd2O3. Energy trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Some authors have reported a similar emission, especially for the bare nanostructured gadolinium oxide. 55 For instance, R. Mohan et al reported a broad emission around 400 nm for cubic Gd 2 O 3 NPs, synthetised using the precipitation method. 56 Hence, its energy can be modulated depending on the employed methodology, particle size, and morphology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have reported a similar emission, especially for the bare nanostructured gadolinium oxide. 55 For instance, R. Mohan et al reported a broad emission around 400 nm for cubic Gd 2 O 3 NPs, synthetised using the precipitation method. 56 Hence, its energy can be modulated depending on the employed methodology, particle size, and morphology.…”
Section: Resultsmentioning
confidence: 99%
“…76 The broadband from 400 to 550 nm may originate from defects or radiative recombination of photogenerated holes with electrons occupying oxygen vacancies. 55,56,62 The emissions caused by defects have been widely discussed for other nanostructured systems, e.g. in ZnO.…”
Section: Pccp Papermentioning
confidence: 99%
“…Nanoparticles and quantum dots. Y. Kuznetsova et al reported the intrinsic defect‐assisted UV‐visible energy conversion in Gd 2 O 3 :Er nanoparticles. M. Skapas et al performed a high‐resolution transmission electron microscopy study of Bi quantum dots in annealed GaAsBi/AlAs multiple quantum wells.…”
mentioning
confidence: 99%